Per una prima edizione ai "Tarocchi" di Emilio Villa - BATTILOCCHI, BIANCA (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Italian, 2019)
My thesis, supervised by Dr Giuliana Adamo, aims to provide the first edition of a still unpublished collection of Tarot texts by the multilingual and visual poet Emilio Villa (1914-2003). My central research question focuses on how the innovative poetry of Villa goads the reader to meditate on the power of the word and on the 'serious game' that language plays. In my philological approach, I examine handwritten material taken mostly from one of the author's archives, consisting of 200 poems in draft form, as well as a jotter detailing the author's literary aims. Written during the 1980s, this material represents the mature phase of his work, and is fundamental to understanding his originality within the context of contemporary literature. It's also an opportunity to discover the poet's modus operandi, his peculiar style of work. Like all the author's poems from the 1950s, his Tarots are not written in a standard Italian but in a linguistic 'pastiche' of French, Italian dialects, as well as fragments of Latin, Greek and Sumerian. In his poems, Villa created surprising new words, cross-language neologisms, puns and paraetymologic games. He also enjoyed experimenting with changeable page settings to accompany the fluidity of his poetic diction; visual constructions that sustain his attempts to extend the potential of language.
APPROVED
Keywords: Emilio Villa/ Italian Poetry/ Tarot Cards/ Multilingual Poetry/ Visual Poetry